2017
DOI: 10.1073/pnas.1707466114
|View full text |Cite
|
Sign up to set email alerts
|

Lethality of MalE-LacZ hybrid protein shares mechanistic attributes with oxidative component of antibiotic lethality

Abstract: Downstream metabolic events can contribute to the lethality of drugs or agents that interact with a primary cellular target. In bacteria, the production of reactive oxygen species (ROS) has been associated with the lethal effects of a variety of stresses including bactericidal antibiotics, but the relative contribution of this oxidative component to cell death depends on a variety of factors. Experimental evidence has suggested that unresolvable DNA problems caused by incorporation of oxidized nucleotides into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 61 publications
6
48
0
Order By: Relevance
“…It has been argued that potential off-target effects are difficult to rule out for perturbations with chemical agents, such as thiourea and bipyridyl (23,24); thus, statements of causality are questionable when such agents are used. Off-target effects are unlikely with enzymatic suppression of ROS, as when catalase is added to agar or when a deficiency of katG (catalase) increases killing (20,26,28). A causal role for ROS in stress-mediated death has also emerged from the effects of mutations in a variety of other genes, most notably genes involved in the processing of 8-oxoguanine in .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been argued that potential off-target effects are difficult to rule out for perturbations with chemical agents, such as thiourea and bipyridyl (23,24); thus, statements of causality are questionable when such agents are used. Off-target effects are unlikely with enzymatic suppression of ROS, as when catalase is added to agar or when a deficiency of katG (catalase) increases killing (20,26,28). A causal role for ROS in stress-mediated death has also emerged from the effects of mutations in a variety of other genes, most notably genes involved in the processing of 8-oxoguanine in .…”
Section: Discussionmentioning
confidence: 99%
“…both quinolone and ROS are known to generate DNA breaks (11,26,28,30,42,43). Treatment with the quinolone nalidixic acid led to rapid accumulation of DSBs; after 1 h treatment, 97% of cells scored positive (Fig.…”
Section: Contribution Of Primary Damage and Damage Repair To Cell Deathmentioning
confidence: 96%
See 1 more Smart Citation
“…It may be possible to distinguish between these biochemically, as the lethality driven by secondary processes can be interrupted by inhibiting protein translation and cell respiration [34] or by metabolic shunting [37]. Cell death emerging from stress-induced death processes was recently studied in an antibiotic-free system using a historically significant fusion protein [64]. The authors demonstrated that the primary consequence of jamming the SecY protein translocation machinery was cell stasis and that cell death instead emerged from downstream events shared with antibiotic lethality, including ROS accumulation and double-stranded DNA damage.…”
Section: Bactericidal Processesmentioning
confidence: 99%
“…However, regardless of the primary cellular target, different bactericidal antibiotics all induce a similar cascade of events that contribute to their lethality in Escherichia coli: accelerated respiration (7); changes in iron and redox metabolism (8); formation of reactive oxygen species (9); oxidative damage of DNA (10), RNA, and proteins (11); and cell death. Interestingly, the same killing cascade is seen in a number of antibiotic-independent killing phenomena, for example, T6SS-effector dependent killing (12) and expression of a toxic fusion protein (13).…”
mentioning
confidence: 97%